Impulsive choice in adults: how consistent are individual differences? - Navarick, Douglas J. (Psychological Record)
With animated cartoons as the reinforcer, college students repeatedly made choices between a schedule providing 15 s of viewing followed by 75 s of waiting and a schedule providing 55 s of waiting followed by 25 s of viewing and then 10 s of waiting. Individual differences in choice behavior were extreme: In the second half of the first session, on at least 70% of the trials, 40% of subjects chose the small (15-s) reinforcer (impulsivity) and 40% the large (25-s) reinforcer (self-control). Each of these subjects continued to choose the same schedule consistently throughout the second session 1 - 49 days later. A briefer small reinforcer (10-s) produced self-control in almost all subjects. Stable individual differences could reflect an interaction between reinforcement variables and “personality.” Reprinted by permission of the publisher.